Awareness Among Dental Undergraduate Students Regarding CAD/CAM Technology in Tripoli Region, Libya - Ahmed Mhanni; Sirageddin Al-hmadi; Seham El-Sawaay (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and objectives: Metal-free ceramic has become increasingly popular as a result of the enormous growth in demand for cosmetic dentistry. Because of this, the majority of dentists began utilising digital technology, which allows them to work faster and produce products with attractive aesthetic and functional outcomes. The field of modern dentistry is moving closer to CAD/CAM (computer-aided design/computer-aided manufacturing) technology. The purpose of this study is to assess undergraduate students' awareness levels, with the aim of comparing the findings to change the curriculum in the future. The study's objectives were to (1) assess awareness among dental undergraduate students and (2) compare it to that of second-, third-, final-, and intern-year dental students. Methods: A cross-sectional, questionnaire-based study was carried out among dental students (second-year students, third-year students, final-year students, and interns) in the Tripoli region that extended to two dental faculties. To determine the sample size, the reference article of a comparable study conducted in India was used. There were 212 participants in this study as a total sample. The authors selected a closed-ended questionnaire. The questions were taken from other studies to clarify and fit the fixed partial denture subject. Statistical Package for Social Sciences (SPSS) version 22 was used to perform the statistical analysis. Descriptive and Chi-square tests were selected. The level of significance was set at 5%. Results: The study involved undergraduate students and interns, with the final-year undergraduate students having the highest response rate (57.1%). The majority of the students, who were in their final year, were aware of digital impressions and CAD/CAM technology. Most of the students stated that zirconium and fixed partial dentures were created using CAD/CAM technology. Prosthodontics is the area of dentistry that uses digital technology the most frequently, and CAD/CAM technology is more accurate than traditional techniques in this area. Conclusions: A large number of those who participated agreed that restorations made using CAD/CAM technology are superior to those made using conventional methods and recommended including CAD/CAM technology in the curriculum.